Transcatheter closure of ruptured sinus of valsalva to left ventricle - Devi A Manuel; Anandaroop Lahiri; Oommen K George (Annals of Pediatric Cardiology, 2016)
We report a rare case of ruptured right sinus of valsalva into the left ventricle (LV). Transthoracic echocardiography showed a marked turbulent flow from the right aortic sinus to the LV. We describe a novel technique of closure of this defect with duct occluder, involving the formation of an arterio-arterial loop, without resorting to the usual arteriovenous loop.